PENGARUH KEMATANGAN EMOSIONAL, KUALITAS KEHIDUPAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI KANTOR KEMENTERIAN AGAMA KABUPATEN BATU BARA - Yunaini .; Agus Supriono; Alfi Hidayati; Asyari .; Dumai Yanti Hutauruk (JRMB (Jurnal Riset Manajemen & Bisnis), 2020)
Problem of this study is how influence of   emotional maturity on employee’s performance. How influence of quality of  work life on employee’s performance. How influence of job motivation on employee’s performance. How influence    emotional maturity, quality of  work life and job motivation on employee’s performance.  The purpose of this study to determine and analyze the effect of   emotional maturity on employee’s performance. Determine and analyze the effect of quality of  work life on employee’s performance. Determine and analyze the effect of job motivation on employee’s performance. Determine and analyze the effect of  emotional maturity, quality of  work life and job motivation on employee’s performance. Sample in the study is 48  employee’s. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis.  The results of the study indicate  emotional maturity variable has a positive and significant effect on employee’s performance.  Quality of  work life variable has a positive and significant effect on employee’s performance. Job motivation variable has a positive and significant effect on employee’s performance.  Emotional maturity, quality of  work life and job motivation variable has a positive and significant effect on employee’s performance.